PENGARUH PELAKSANAAN PROSEDUR KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN PRODUKSI TANDAN BUAH SEGAR DI PT. CERENTI SUBUR - KUANTAN SINGINGI - Fitri "; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
FISIP Universitas RiauAbstractWorkforce in an organization is something that is very important andcomplex in nature and is a major factor. If the terms of the stipulation,procurement, placement and development. Key to the success of an enterprise isnot only lie in the equipment used, but also on the human and other resources.They will determine whether or not worked so satisfied workforce remains thesubject and purpose of personnel management. Job performance is a result ofwork achieved in executing the tasks assigned to him were carried out on theskills, experience and seriousness as well as time. In other words that theperformance was the work achieved by a person in carrying out the tasks assignedto him in accordance with defined criteria.This research was conducted at PT. Cerenti Subur - Kuantan Singingi. Thepurpose of this study was conducted to determine the effect of the implementationof the working procedures and discipline of work on employee performance in theproduction of PT. Cerenti Subur - Kuantan Singingi.In this study, the methodology used is descriptive and quantitative with SPSS. Todetermine the sample using the formula Slovin, methods of sampling withaccidental sampling. Techniques of collecting data through interviews,observation and questionnaires.From the results of data analysis include validity, reliability, classicalassumptions and multiple linear regression, the implementation of workprocedures in this study included three indicators are situational, maintainingstability and modern and the discipline of work is represented by three indicators,namely on time, adherence to regulations and ability to maintain tools. Each has avariable interrelated and positive effect on employee performance in theproduction of PT. Cerenti Subur - Kuantan Singingi.Keyword: Working Procedures, Work Discipline, Work Performance